About direct object offense under art. 2392 CC of Ukraine (misappropriation of lands of water fund in especially large amounts) - Кумановський, М. В. (Problems of legality, 2013)
Defines the direct object of the crime stipulated in Article st. 2392 СС of Ukraine (misappropriation of lands of water fund in especially large amounts). Investigate its structure and mechanism of injury.